Characterizing the zonally asymmetric component of the SH circulation - Hobbs, William R.; Raphael, Marilyn N. (Climate Dynamics, 2010)
Much research concerning the Southern Hemisphere (SH) zonally asymmetric circulation has focused on the Pacific-South American mode (PSA) or the major zonal waves. However, these large-scale decompositions may mask important local variability. In this paper the month-to-month variability explained by the zonal waves 1 and 3 is examined, and an alternative representation of the SH circulation is presented based on two quasi-stationary anticyclones in the sub-Antarctic western hemisphere. These anticyclones are related to the zonal waves, but features of their variability are masked by the zonal wave decomposition; in particular, the anticyclones’ strengths are not positively covariant. They are also compared with the leading Principal Components of the SH atmosphere. We show that they capture variance independent of the Southern Annular Mode. Additionally, they explain a generally greater fraction of the variability than the PSA, and in a manner that also includes information regarding spatial variability. These results have implications for analysis of the atmospheric-forcing of western Antarctic climate.